Anti-inflammatory effects of endothelin receptor blockade in left atrial tissue of spontaneously hypertensive rats. (October 2022) - Bukowska, A.; Nikonova, Y.; Wolke, C.; Lendeckel, U.; Kockskämper, J.; Goette, A.
Abstract: Objective: In spontaneously hypertensive rats (SHR) atrial remodeling has been shown to involve increase in endothelin (ET) signaling. Furthermore, inflammatory processes may further contribute to tissue remodeling. The aimed of this study was to investigate whether an endothelin receptor antagonist, macitentan, could reduce left atrial (LA) remodeling in arterial hypertension. Methods: Molecular characterization of atria was performed in SHR at the age of 8 months and their age-matched normotensive control rats (WKY). SHR were treated with macitentan and, for comparison with a blood pressure reducing drug, with doxazosin. After two months of treatment, molecules involved in endocardial inflammation and atrial calcium handling were assessed. The molecular changes provoked by rapid-pacing (RAP) were analyzed in atrial tissue slices. Results: Doxazosin reduced the systolic blood pressure compared with the untreated SHR (159 ± 26 vs. 176 ± 17; P < 0.05) or macitentan (vs. 189 ± 21; P < 0.05). Macitentan lowered the increased levels of atrial ET-1 and abrogated the pacing-induced upregulation of preproET-1-mRNA in atrial slices from SHR. Macitentan reduced the elevated levels of atrial 8-isoprostanes, the increased expression of pro-inflammatory ICAM-1 and IL-8, the phosphorylation of MAP kinases, ERK and p38, the phosphorylation of NF-κB and the expression of VCAM-mRNA. Major Ca 2+ -regulating proteins and markers of hypertrophy and fibrosis, however, were not affected. Doxazosin elicited similar changes, except for the alterations in ET-1 levels, NF-κB phosphorylation and VCAM-mRNA. Conclusion: Macitentan reversed pro-inflammatory remodeling in hypertensive atria in a blood pressure-independent manner, which might prevent endocardial dysfunction and thereby, thrombogenesis in arterial hypertension.